Determinants of lending behaviour in Malaysia / Nur Atikah Mohd Lani - Mohd Lani, Nur Atikah (2017)
With the unstable economic condition in Malaysia nowadays, financial institutions have a lot of doubts as to how much lending rates they can offer because the limit is whatever the market will bear but will the market participants be able to bear? As we know, financial institutions do grant loans and advances to individuals, business organizations as well as government in order to enable them embark on investment and development activities as a mean of aiding their growth in particular or contributing toward the economic development of a country in general but this raises a question whether the objective can be achieved successfully or not. Consequently, the main objective of the study is to find out the determinants of the lending behaviour in Malaysia by using time series in Multiple Linear Regression model for empirical analysis from year 1986 to 2015. The lending behaviour in Malaysia are measured by Commercial banks and other lending in Malaysia. Besides, this research uses gross domestic product, lending interest rates, reserves requirement, inflation, exchange rates, and risk premium as the determinants for lending behaviour in Malaysia. However, the result reveals that there is only Inflation, Exchange Rates and Risk Premium has significant relationship with lending behaviour in Malaysia whereas gross domestic product, lending interest rates and reserves requirement are not significant with lending behaviour in Malaysia. Since, Malaysian economic market start going bad, we need to focus on more factors in this issue to measure the effectiveness of Malaysian monetary policy.